1981
DOI: 10.1007/bf00544604
|View full text |Cite
|
Sign up to set email alerts
|

Acetylator phenotyping: A comparison of the isoniazid and dapsone tests

Abstract: A comparison was made between the results of acetylator phenotyping by isoniazid (INH) half-life measurements based on 5 samples (0-6 h), and by determination of the ratio of monoacetylated (MAD) to unchanged dapsone (DDS) in a single sample obtained 3 h after dapsone intake. In each of 44 subjects examined, there was unequivocal agreement about classification of the subject as a rapid (INH t1/2 less than 2 h; MAD/DDS greater than 0.3) or slow (INH t1/2 greater than 2 h; MAD/DDS less than 0.3) acetylator. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 6 publications
2
18
0
1
Order By: Relevance
“…Application of the Hardy Weinberg Law indicated that the frequency of the allele controlling recessive slow acetylators (q) was 0.360 and for the allele controlling dominant rapid acetylators (p) it was 0.640. (Reidenberg et al, 1975;Carr et al, 1978;Hanson et al, 1981). between the acetylation ratio and plasma MADDS concentration (Figure 2b), there was a highly significant (P < 0.001) difference in the mean value for plasma MADDS concentration between the two phenotypes (Table 1).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Application of the Hardy Weinberg Law indicated that the frequency of the allele controlling recessive slow acetylators (q) was 0.360 and for the allele controlling dominant rapid acetylators (p) it was 0.640. (Reidenberg et al, 1975;Carr et al, 1978;Hanson et al, 1981). between the acetylation ratio and plasma MADDS concentration (Figure 2b), there was a highly significant (P < 0.001) difference in the mean value for plasma MADDS concentration between the two phenotypes (Table 1).…”
Section: Resultsmentioning
confidence: 90%
“…Nonetheless, isoniazid, sulphamethazine or DDS have been shown to give concordant results on individual phenotyping (Gelber et al, 1971;Reidenberg etal., 1975;Hanson etal., 1981), sex and age do not appear to have important influences on phenotyping (Evans et al, 1960) and the frequency of slow acetylators in patients with tuberculosis does not differ from that in normal healthy subjects (Evans, 1986). DDS has been used as an adequate test probe for determining acetylator phenotype (Reidenberg et al, 1975;Carr et al, 1978;Hanson et al, 1981;Philip et al, 1984;Clark, 1985). The plasma ratio of MADDS to DDS at 3 h after a single oral dose of 100 mg of DDS is commonly used and is considered to be clinically acceptable (Reidenberg et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of monoacetyldapsone (MAD) to dapsone was determined in plasma samples using high performance liquid chromatography (7). When compared with the isoniazid method of phenotype determination, a MAD:DDS ratio of <0.3 indicates the slow acetylator phenotype, a ratio of >0.35 indicates the fast acetylator phenotype, and ratios of 0.3-0.35 cannot be used to determine acetylator phenotype (8,9). Data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In 1971, Gelber et al determined the ratio of monoacetyldapsone (MADDS) and dapsone (DDS) (Rumble et al, 1981) (Hanson et al, 1981). This was followed by alkalinisation, extraction into diethyl ether and evaporation to dryness of an aliquot of the organic phase.…”
Section: Introductionmentioning
confidence: 99%